2019
DOI: 10.1111/1346-8138.15204
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety data for dabrafenib and trametinib combination therapy in Japanese patients with BRAF V600 mutation‐positive advanced melanoma

Abstract: We conducted a retrospective investigation of the efficacy and safety of dabrafenib and trametinib combination therapy in Japanese patients with BRAF V600 mutation‐positive advanced melanoma in real‐world clinical practise. The study analyzed 50 patients who received dabrafenib and trametinib combination therapy for BRAF V600 mutation‐positive advanced melanoma in our hospital (26 men and 24 women, aged 21–86 years, inclusive; median age, 53 years). The response rate was 72.3%, with complete response (CR) achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
3
9
2
Order By: Relevance
“…Multivariate analysis of baseline factors demonstrated that LDH levels and the number of metastatic sites were significantly associated with PFS and OS, corroborating previous randomized trials in Caucasian melanoma patients ( 9 , 25 , 26 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Multivariate analysis of baseline factors demonstrated that LDH levels and the number of metastatic sites were significantly associated with PFS and OS, corroborating previous randomized trials in Caucasian melanoma patients ( 9 , 25 , 26 ).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, patients with fewer lines of previous therapy, no previous immunotherapy, fewer metastatic organ sites and no visceral disease might gain more survival benefits from the combined regimen. Furthermore, while analyzing survival in patients with different tumor response in this trial, optimal outcomes were observed in individuals who achieved CR, confirming previous analyses ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 85%
“…16 The response rate of our study population was 66%, which was almost similar to 67% in clinical trial settings 16 and 72% from the Japanese study. 17 At a median follow-up of 23 months, the median PFS of the cohort of our patients was 9.3 months. It is almost similar to the updated analysis of the pivotal landmark trial where it was 11.1 months.…”
Section: Discussionmentioning
confidence: 75%
“…Among BRAF inhibitor-naïve patients, the ORR was 67.3% and median PFS was 7.5 months. In a Japanese study [19] that included only 50 patients, the response rate was 72.3%, with CR achieved in 8 cases (17.0%), PR in 26 (55.3%), SD in 9 (19.1%) and PD in 4 (8.5%).…”
Section: Discussionmentioning
confidence: 98%